Phosphorus sources residual effects on tifton 85 production and nutritive value cultivated in a tropical weathered soil - Franco, Henrique Coutinho Junqueira [UNESP]; Borges, Bernardo Melo Montes Nogueira; de CASTRO, Sérgio Augusto Quassi; Megda, Michele Xavier Vieira; Megda, Marcio Mahmoud; Garside, Alan L.; Coutinho, Edson Luiz Mendes [UNESP] (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2020)
Acid reactions and low available phosphorus in tropical soils limit forage yield. The aim was to evaluate soil chemical characteristics pH, P and Mg, forage nutritive values, critical soil and plant P levels and the residual effect of each source. The experiment was in a greenhouse with a Rhodic Haplustox, loam texture. Experimental design was a 5 x 4 factorial with five replicates which phosphate fertilizers were triple superphosphate, reactive rock phosphates Gafsa and Arad, and fused magnesium phosphate powder and coarse, applied at rates of 30, 60, 90 and 120 mg kg-1 P and a control treatment without P. The effectiveness of rock phosphates increased due to their residual effect. The coarse fused magnesium phosphate resulted in the lowest efficiency. The P critical level in soil and plant were 18 mg kg-1 and 2.4 g kg-1, respectively. The increase of phosphorus rates provided an increase in crude protein content.
Efeito residual de fontes de fósforo na produção e valor nutricional do tifton 85 cultivado em solo tropical
Keywords: Bermudagrass; Critical level; Pasture; Phosphate rock